Preparation and Characterization of Cu nanoparticles by Laser Ablation in NaOH Aqueous Solution (International Journal of Current Engineering and Technology, 2014)
In the recent years, laser ablation in liquid has become an increasingly important technique for the fabrication of NPs . this paper reports our recent studies on the generation of Cu NPs by ablation of metal targets in aqueous environments using Q-switch Nd-YAG laser (λ=532nm) immersed in NaOH (0.1M) .solution of NPs is found stable in the colloidal form for a long time. The Surface topography studied by atomic force microscopy revealed wider size distributions, with particle sizes (98.43nm to 115.99nm )and shape were measured by using SEM shows spherical shape while the composing of the prepared nanoparticle were determined by X-ray ,UV-Visible spectroscopy has been employed for the optical properties .the UV-VIS spectrum of produced solution shows red shifted in the peak position .
Keywords: Laser Ablation, Collide Nanoparticles, Aqueous solution, Cu nanoparticles